2x+7-4x=16-19x+17x-9

Simple and best practice solution for 2x+7-4x=16-19x+17x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7-4x=16-19x+17x-9 equation:


Simplifying
2x + 7 + -4x = 16 + -19x + 17x + -9

Reorder the terms:
7 + 2x + -4x = 16 + -19x + 17x + -9

Combine like terms: 2x + -4x = -2x
7 + -2x = 16 + -19x + 17x + -9

Reorder the terms:
7 + -2x = 16 + -9 + -19x + 17x

Combine like terms: 16 + -9 = 7
7 + -2x = 7 + -19x + 17x

Combine like terms: -19x + 17x = -2x
7 + -2x = 7 + -2x

Add '-7' to each side of the equation.
7 + -7 + -2x = 7 + -7 + -2x

Combine like terms: 7 + -7 = 0
0 + -2x = 7 + -7 + -2x
-2x = 7 + -7 + -2x

Combine like terms: 7 + -7 = 0
-2x = 0 + -2x
-2x = -2x

Add '2x' to each side of the equation.
-2x + 2x = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2(2)-3y=18 | | 6(3t+7)=96 | | 3(6t-6)=108 | | 5(4+2x)=90 | | 7(9+3k)=210 | | 2(1)-3y=18 | | 2(0)-3y=18 | | 6x+17=2x+13 | | 2(9-7d)=-10 | | 6(-3-6n)=-198 | | 11.3d+2.5=1.3d | | 4(-7-6n)=-268 | | 2(3+4a)=-42 | | 7(-4k+6)=-182 | | 3(2+7a)=195 | | -2x-4=-9 | | 6-3(3x-2)=15 | | 2(-1)-3y=18 | | 4(5-b)=24 | | 6(-5+7d)=-30 | | 2(-2)-3y=18 | | 5(1a+6)=30 | | b-14.72=18.45 | | 4(4+3m)=16 | | 2(-5n+4)=-62 | | -20+x=x+16 | | 7(9+3m)=168 | | 4(-6t-1)=-148 | | 2(7-2t)=42 | | 3(9-2d)=3 | | df=g-10 | | 6(-2t+8)=-84 |

Equations solver categories